TINDAK TUTUR ASERTIF DALAM PIDATO PELANTIKAN DONALD TRUMP DI GEDUNG CAPITOL WASHINGTON DC - Irawan Syahdi (TELAGA BAHASA, 2017)
Illocutionary acts serve not only to inform but also affect the hearers to dosomething . This study discusses the assertive illocutionary acts in Donaldtrump's inauguration speech at Capitol Building in Washington DC, onFriday January 20, 2017. This is a descriptive qualitative study usingspeech acts theory proposed by Searle and others. The technique used inthis study of speech acts are noting and references. From the results ofstudies conducted there are some functions of assertive speech acts found in the speech that is: state, inform, assert, suggest, complain, boast, andpromise.